Factors Affecting Secondary Traumatic Stress Disorder among Search and Rescue Team in Makassar - Sri Rahayu; Elly Lilianty Sjattar; Tuti Seniwati (Indonesian Contemporary Nursing Journal, 2021)
Introduction: Disaster is an unwanted event and usually occur suddenly and is accompanied by many victims. Disasters can have many impacts, both physical and psychological. The psychological impact that can arise on disaster victims is called Post Traumatic Stress Disorder (PTSD). Not only on the victim, the person who served as a helper also can have psychological disorders. Psychological disorders in these helpers are called Secondary Traumatic Stress Disorder (STSD). This study was aimed to  identify factors that influence the incidence STSD the Search and Rescue (SAR) teams in universities and BASARNAS Makassar. Method: This research is a quantitative study with a cross-sectional approach using total sampling techniques the samples in this study were all sar and basrnas member (n=60) who agreed to be the respondent and have involved in rescue activity on one last year. Data is collected by distributing questionnaires. Questionnaires used were Secondary Traumatic Stress Scale and Crisis Support Scale.  The statistical test used Chi square test, Mann-Whitney U test and logistic regression analysis. Result: The study showed that there was a relationship between the frequency of exposure, social support, and the length of work (p<0,05) and the incidence of STSD. However, the type of exposure has no significant relationship with the incidence of STSD. Conclusion: Social support is the most significant factor compared to the frequency of exposure, the type of disaster and length of work / joining. This research is expected to provide additional information on STSD risk factors. For future researchers, in order to examine other variables which is trauma history and coping mechanism the SAR team to experience symptoms of STSD